1998
DOI: 10.1080/00319109808032788
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxation of Binary Mixtures of Glycerol with Three Monohydric Alcohols

Abstract: The dielectric spectra of the following liquid mixture systems have been measured over the whole absorption region: Glycerol (Gly)/n-butanol, Glylr-butanol (both at 20°C) and Gly/guaiacol(20,40 and 60 " C ) . Thc results are comparatively discussed with regard to hetero-interactions, taking into consideration the possibility of internal hydrogen bonding in the case of guaiacol and. generally. of steric constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…As dipole moment of solvent (dioxane) is very small (μ = 0.97D), [17] the interaction between third pair can be neglected. Therefore, interaction between co-solvent-dioxane [18][19][20][21][22][23][24][25] can provide insight to understanding the exact nature of -OH group through molecular interaction in the liquid. S. Czerkas et al [24] have reported the variation of viscosity and activation energy against mole fraction of alcohol in dioxane.…”
Section: Introductionmentioning
confidence: 99%
“…As dipole moment of solvent (dioxane) is very small (μ = 0.97D), [17] the interaction between third pair can be neglected. Therefore, interaction between co-solvent-dioxane [18][19][20][21][22][23][24][25] can provide insight to understanding the exact nature of -OH group through molecular interaction in the liquid. S. Czerkas et al [24] have reported the variation of viscosity and activation energy against mole fraction of alcohol in dioxane.…”
Section: Introductionmentioning
confidence: 99%